2015
DOI: 10.1084/jem.20141015
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-related factors as biomarkers in EAE and MS

Abstract: Using a mouse model of multiple sclerosis (MS), the authors show that neutrophils expand in the bone marrow and accumulate in the circulation before clinical onset of disease. Early in disease development, neutrophils infiltrate the CNS, which is suppressed by G-CSF receptor deficiency and blockade of CXCL1 to ameliorate disease. In patients with MS, systemic expression of neutrophil-related mediators correlates with new lesion formation, lesion burden, and clinical disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
223
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(237 citation statements)
references
References 76 publications
13
223
0
1
Order By: Relevance
“…3 In addition, CXCL5 is a biomarker of T-helper 17-mediated autoimmune diseases, such as multiple sclerosis, rheumatoid arthritis and glomerulonephritis. 4 In our present case, the serum level of sCD163 and CXCL5 began to increase 6 weeks after the administration of nivolumab, suggesting the existence of autoimmune-like reaction. To our knowledge, there is no English-language report describing an idiopathic ACTH deficiency in nivolumab-treated patients except for hypophysitis cases that are not further classified 5 and may include idiopathic ACTH deficiency cases.…”
supporting
confidence: 50%
“…3 In addition, CXCL5 is a biomarker of T-helper 17-mediated autoimmune diseases, such as multiple sclerosis, rheumatoid arthritis and glomerulonephritis. 4 In our present case, the serum level of sCD163 and CXCL5 began to increase 6 weeks after the administration of nivolumab, suggesting the existence of autoimmune-like reaction. To our knowledge, there is no English-language report describing an idiopathic ACTH deficiency in nivolumab-treated patients except for hypophysitis cases that are not further classified 5 and may include idiopathic ACTH deficiency cases.…”
supporting
confidence: 50%
“…9 Accumulating clinical and experimental evidence implicates neutrophils in the pathogenesis of MS and EAE. [11][12][13]26,27 Upon immunization, Cre mice developed EAE with disease onset at ;7 to 14 days and peak at ;21 to 28 days ( Figure 2D). In contrast, K4-cKO mice showed a delayed onset and significant reduction in severity of EAE despite 100% disease incidence ( Figure 2D; supplemental 7A).…”
Section: Myeloid Klf4 Deficiency Protects Animals From Eaementioning
confidence: 99%
“…10,11 Neutrophils in the blood of MS patients exhibit a primed phenotype, and both neutrophil number and biomarkers of neutrophil activity increase during relapses. 11 In EAE, neutrophils comprise a significant percentage of CNS-infiltrating leukocytes prior to disease onset and relapse, and disease was ameliorated when neutrophils were depleted prior to, but not after, disease onset or relapse, suggesting important neutrophil function during the initial formation of MS lesions. 12 It has been reported that neutrophils may play a role in mediating blood-brain barrier breakdown.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, neutrophil infiltration is prominent in early active demyelinating spinal cord (SC) lesions of neuromyelitis optica patients (17). Furthermore, a recent study demonstrated that systemic expression of neutrophil-associated factors, including CXCL1, CXCL5, and neutrophil elastase, correlated with measures of MS lesion burden and clinical disability (18), further supporting the involvement of neutrophils in neuroinflammatory diseases. MS is a heterogeneous disease in terms of inflammatory lesions (19,20).…”
mentioning
confidence: 95%